Strengthening Character Education Through Extracuricular Activities Paskibra For High School In Bandung City - puri, Nurtania; Sanusi , Achmad; roji, Fahru; Sauri , Supyan (International Journal of Educational Research & Social Sciences, 2022)
Since the issuance of the Presidential Decree and the Minister of Education and Culture concerning Strengthening Character Education to date, what has happened has tended to be more about knowledge of character education, in its implementation many have occurred in several educational units. The process of understanding based on data in the field, practice of behavioral attitudes, and continuous self- habituation every day that consistently shows these characters, has not shown a real and significant impact. It is necessary to make breakthrough efforts to strengthen so that character education does not become just like a subject or knowledge about the characters mentioned earlier, but rather how character strengthening is really understood, carried out, and accustomed to being repeated in daily life. It can also be implemented consistently by schools and have a real impact. This study focuses on Paskibra Bandung extracurricular activities at the high school level which are directly an effort to improve student consistency in the implementation of strengthening character education. The purpose of this research is to describe how Strengthening Character Education through Paskibra Bandung City Extracurricular Activities at the high school level which focuses on a consistent diary of self-understanding, can increase the consistency of the practice of Core Competence 1 (Spiritual Attitude) and Core Competence 2 (Social Attitude) so that it shows commitment The practice of behavioral attitudes according to the character can be understood, carried out, and accustomed to at any time, continuously every day, using a descriptive qualitative approach so that it intensively and in detail describes the symptoms and phenomena being studied. The research questions posed are: (a) How are the goals and programs to increase the strengthening of character education through extracurricular activities of Paskibra Bandung City at the high school level using a diary of self-understanding in improving the consistency of KI1 and KI2 practices; (b) How are the implementation of strengthening character education through Paskibra Bandung extracurricular activities at the high school level using a diary of self-understanding in improving the consistency of KI1 and KI2 practices; (c) What are the problems in implementing strengthening character education through extracurricular activities of Paskibra Bandung City at the high school level using a diary of self-understanding in improving the consistency of KI1 and KI2 practices; (d) How are the solution to the problem in strengthening character education through extracurricular activities Paskibra Bandung City at the high school level using a diary of self-understanding in improving the consistency of KI1 and KI2 practices. The findings in this study are the low commitment, consistency, motivation, awareness, and self-understanding of students due to the character education strengthening program that has not been implemented in a comprehensively integrated and sustainable manner. Based on this, this study recommends the need to make a grand design or model of coaching and strengthening character education exercises to implement consistently, comprehensive, integrated, and sustainable good practice habits.